TINGKAT KEBERHASILAN MEDIASI OLEH HAKIM DAN NON-HAKIM DI PENGADILAN AGAMA PURWODADI TAHUN 2019 - Rizky, Rizky Kurniyana; Muchamad Coirun Nizar (Indonesian Association of Islamic Family Law Lecturers, 2021)
In human life, conflicts that cannot be avoided often occur. Among the many conflicts or disputes are Islamic civil cases. As for the authority and duty to examine, hear and decide Islamic civil cases at the first level is the Religious Court. And all disputed cases that are submitted to the Religious Courts must first seek a way of conciliation through the mediation process. In a court there is a mediator who is in charge of leading a mediation process. Including the Purwodadi Religious Court, it has a mediator who comes from two elements, namely a mediator who comes from the judge's element and the mediator who comes from the non-judge element. The results of this study state that the mediation process at the Purwodadi Court during 2019 was carried out by judge mediators, namely during January to April and was carried out by non-judge mediators, namely during May to December. Meanwhile, the success rate of mediation carried out by non-judge mediators was higher at 4% when compared to the success rate of mediation by judge mediators which was only 2%. The difference in the level of success of the mediation by the two different mediators is certainly influenced by several factors, namely the mediator factor, the factors of the parties and their families and the factor of the community's mindset.